2020
DOI: 10.21203/rs.3.rs-108417/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental and numerical study of coal-rock bimaterial composite bodies under triaxial compression

Abstract: The paper presents experimental and numerical investigations on the response of rock-coal, coal-rock, and rock-coal-rock bimaterial composite structures under triaxial compression. The triaxial compression experiments are conducted under confining pressures in the range of 0–20 MPa. The resulting inside fracture networks are detected using X-ray-based computed tomography (CT). The experimentally observed data indicate that the mechanical parameters of the rock-coal-rock composites are superior to those of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The mechanical parameters of the coal and rock mass were very important to the accuracy of the numerical simulation results 22,23 . Mohammad et al 24 suggested that the average stiffness of a numerical model should be 0.469 of the laboratory stiffness, and the average uniaxial compressive strength of the model should be 0.284 of the laboratory strength.…”
Section: Establishment Of Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical parameters of the coal and rock mass were very important to the accuracy of the numerical simulation results 22,23 . Mohammad et al 24 suggested that the average stiffness of a numerical model should be 0.469 of the laboratory stiffness, and the average uniaxial compressive strength of the model should be 0.284 of the laboratory strength.…”
Section: Establishment Of Numerical Modelmentioning
confidence: 99%
“…The mechanical parameters of the coal and rock mass were very important to the accuracy of the numerical simulation results. 22,23 Mohammad et al 24 suggested that the average stiffness of a numerical model should be 0.469 of the laboratory stiffness, and the average uniaxial compressive strength of the model should be 0.284 of the laboratory strength. Cai et al 25 suggested that the elastic modulus, cohesion, and tensile strength of the coal and rock mass could be estimated to be 0.10-0.25 of the laboratory test results.…”
Section: Engineering Backgroundmentioning
confidence: 99%
“…This indicates that the rock weaks with water content, which increases the internal damage and ultimately reduces the dissipation strain energy rate. In other words, the higher the strength more will be the dissipation strain energy rate and vice versa [72][73][74][75][76][77][78][79].…”
Section: Strain Energy Ratementioning
confidence: 99%
“…Under the experimental conditions of low confining pressure or high impact load, gas-bearing coal showed crushing failure, while under other experimental conditions, coal samples showed an axial tensile failure mode [37]. Shen Rongxi et al conducted research on the peak stress and strain of the dynamic parameters of coal samples under uniaxial and triaxial static load prestress and the triaxial static load prestress and strain rate [38]. Wang Lei et al studied the dynamic stress and strain characteristics of a coal body when the gas pressure was 0, 0.5, 1.0, and 1.5 MPa.…”
Section: Introductionmentioning
confidence: 99%